Evaluation analysis of the special autonomy fund assistance program in improving the welfare of indigenous Papuans in Kwamki Narama District, Mimika Regency - Ambate, Altwer; Marlissa, Elsyan R.; Hutajulu, Halomoan (Journal of Multidisciplinary Academic Business Studies, 2025)
Purpose: This study evaluates the effectiveness of the Special Autonomy Fund Assistance Program in improving the welfare of Indigenous Papuans in the Kwamki Narama District, Mimika Regency, focusing on education, health, and the economy. Method: A descriptive quantitative approach was applied with 100 respondents from 10 villages, selected using the Slovin formula. Data were gathered through Likert-scale questionnaires and in-depth interviews with key stakeholders and analyzed using descriptive statistics to assess welfare improvements. Results: The findings show improvements in education (mean = 3.67) and health (mean = 3.85), reflecting better access to schools, educational support, and healthcare services. However, the economic dimension showed limited progress (mean = 3.13), with minimal impact on job opportunities, income, and household needs. The overall welfare score was 3.55, suggesting a moderately positive perception of the program. Conclusions: The program has effectively enhanced education and health but has not significantly improved economic empowerment of women. Broader strategies are needed to strengthen economic opportunities and achieve sustainable and equitable welfare outcomes. Limitations: The findings rely on perceptions within one district, limiting generalization to other Papuan regions, and do not consider qualitative factors such as cultural or governance dynamics that may affect the outcomes. Contribution: This study contributes empirical evidence to the discussion on regional autonomy, highlighting the partial success of Papua’s Special Autonomy Fund and the need for policy adjustments to better integrate economic empowerment and social development.